Comparative Study of the Starch Digestibility of Araucaria angustifolia and Araucaria araucana Seed Flour - Conforti, Paula Andrea (2008)
Araucaria angustifolia and Araucaria araucana are South American conifers; former grows in the southern and southeastern Brazil and northeastern Argentina and latter grows in mountainous region of southern Argentina and Chile. Their seeds have been consumed by the natives for a long time and presently, and araucaria seed flour is used to prepare traditional dishes as ?alfajores?. In this work, the characteristics, proximate composition and in vitro starch digestibility were studied in both seeds. The main component of the seed is starch, with starch content higher in A. angustifolia. The disruption and collapse of the starch granules after boiling the seeds was much more evident in A. angustifolia, probably due to their lower fibre content. This can explain the higher digestibility of A. angustifolia starch with respect to A. araucana.